Comparison of GeneXpert MTB to Mycobacterium tuberculosis culture in children with tuberculosis - Betty Agustina; Cissy Kartasasmita; Dany Hilmanto (Paediatrica Indonesiana, 2019)
Background Diagnosing tuberculosis (TB) in children is difficult. Typical methods take a long time to achieve results, or have a low sensitivity. GeneXpert is a nucleic acid amplification test used to identify Mycobacterium tuberculosis bacteria (MTB) in only 2 hours. Objective To compare the sensitivity and specificity of GeneXpert MTB to MTB culture in children with TB, and to assess factors associated with GeneXpert MTB test in predicting which children were likely to have positive results. Methods This descriptive, analytical study was done in children with suspected TB, aged 1 month to 18 years in Hasan Sadikin Hospital, Bandung, West Java, from January 2016 to December 2017. The data were taken from the medical records and included age, gender, nutritional status, symptoms of TB, chest x-ray, and tuberculin test results. The GeneXpert MTB test was compared to cultures from the same patient, with regards to sensitivity, specificity, and agreement using Kappa index. We analyzed factors associated to GeneXpert MTB test using logistic regression analysis. Results From 454 inpatients and 1,750 outpatients with suspected TB, there were 251 children who were tested by MTB culture and 722 children tested by GeneXpert MTB. Of the 70 cases who met the inclusion criteria and underwent both tests, factors associated with positive GeneXpert MTB results were age 10 to 18 years, female gender, and positive tuberculin skin test (TST). The GeneXpert MTB test showed sensitivity 78.9% (95%CI 56.7 to 91.5) and specificity 86.3% (95%CI 74.3 to 93.2), with accuracy of 84.3% (95%CI 74 to 91), and agreement value of Æ™=0.62 (95%CI 41.6 to 82.7). Conclusion Specificity of GeneXpert MTB is higher than its sensitivity compared to TB cultures in children. The tests were in good agreement. Age 10 to 18 years had the strongest association with positive GeneXpert MTB results.